A Review of the Book "Field Archaeology: An Introduction - amirsadegh naghshineh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Many books have been written about field archaeology universally, but the number of books published on this subject in Iran is rare. One of the books published on this area in Iran, is "Field Archaeology: An Introduction" by Peter L. Drewett which has been translated into Persian by Hojjat Darabi. The book has been published in the field of archeology as an academic textbook for the course of "Methods of Archaeological Excavation and Survey", but does not cover all the topics discussed in this course. One of the strong points of the book is that various discussions on the archaeological excavation are briefly presented in a rational and understandable order. In addition, the Persian translation is fluent, although a careful editing may even improve its quality. The main weak points of the book are the lack of attention to the archaeological survey, a close link with the archaeological issues of Iran and the Middle East, and the lack of necessary parts such as introducing sources for further study. Also, a summary and conclusion at the end of each topic could help the reader. All in all, the book can be used as a guide for archaeological excavation, but it suffers from some deficiencies to be considered as a textbook.